Redistribution and insurance in welfare states around the world - Charlotte Bartels; Dirk Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Redistribution across individuals in a one-year-period framework is an empirically intensely studied question. However, a substantial share of annual redistribution might turn out to serve individual insurance in a longer perspective. In particular, public pensions, that smooth incomes over the life-cycle and are funded by high taxes, play an increasingly important role in welfare states with aging societies. This paper investigates to what extent long-run redistribution diverges from annual redistribution in welfare states of different types. Exploiting panel data from the Cross-National Equivalent File (CNEF) for Australia, Germany, Korea, Switzerland, the United Kingdom and the United States, we find that supposedly highly redistributive welfare states like Germany provoke comparably less redistribution between individuals in the long-run than the United Kingdom or the United States. Regression results show that a higher share of elderly is associated with higher annual redistribution, but with less long-run redistribution between individuals.
Keywords: D31; D63; H53; H55; I38; 330; welfare states; redistribution; insurance